BANKING THE UNBANKED A PERCEIVED RECIPES FOR POVERTY ERADICATION PROGRAM: INDUCTION OF A NEW ISLAMIC MICROFINANCE MODEL IN NIGERIA - L.A., Olorogun (Bank Indonesia, 2018)
This study focuses on efforts to enhance financial inclusion program through the educational orientation development in the Nigerian Islamic finance industry. A Closed User Group (CUG) consisting of Muslims across Nigeria financial educational induction program formed the study sample. The formation of the CUG sought to establish an Islamic compliant financing model that would be effective at the grassroots level in the wake of the failure of microfinance programs to deliver the much needed poverty eradication. To this end, we developed a questionnaire and conducted a financial management induction and education workshop over a period of three days. On the third day, participants were given a questionnaire, from which the results showed that proper education and adjustment to the current available model of microfinance would bring about poverty eradication and that in terms of educational traits building of staff within a typical Islamic financial institution. Future research should look into transformation of personality vices affecting financial institutions as a whole.